THE ROLE OF THE POLICE IN PREVENTING CORRUPTION CRIMES IN INDONESIA - M. Luqman Hakim Siregar; Yasmirah Mandasari Saragih; Kasim; Robert Napitupulu; Roland Banjarnahor (RADJA PUBLIKA, 2023)
This article aims to find out the role of the police in preventing criminal acts of corruption in Sumatra and what the police's efforts are in handling criminal acts of corruption in the North Sumatra region. This writing is motivated by problems in the area of ​​the North Sumatra regional police institution in the police position and wants to know more about the police in dealing with the problem of criminal acts. The research method used is the Normative Juridical method with a descriptive analysis approach. The results of this research are that the police's authority to prevent criminal acts of corruption is regulated in Law no. 2 of 2002 as stated in their duties and responsibilities in maintaining security and order, enforcing the law, providing protection, guidance and service to the community even when handling extraordinary criminal cases. Meanwhile, in carrying out investigations, the police and the Corruption Eradication Committee (KPK) also carry out investigations into complaints and further systematic handling is carried out by looking at operational procedural standards.